2016
DOI: 10.1039/c5ra22463b
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of pH-responsive dextran-g-poly(lactide-co-glycolide)-g-histidine copolymer micelles for intracellular delivery of paclitaxel and its antitumor activity

Abstract: Herein, dextran (DX) was conjugated with poly(lactide-co-glycolide) (PLGA) and histidine (His) to prepare a pH-responsive nanocarrier, dextran-g-poly(lactide-co-glycolide)-g-histidine (HDP) micelles, for the delivery of antitumor drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Established by now main methods for dextran nanoparticle preparation include: the cross‐linking in reverse micelle (water–paraffin emulsion), however, in this case the particle sizes are difficult to control; the dextran oxidation, the multistage formation, and purification of dextran nanoparticles being the main disadvantage of this method; the self‐assembly of copolymers and conjugates based on dextran. This approach suggests the complicated synthetic procedures of dextran modification . Moreover, the absence of cross‐linking in the assemblies obtained may lead to the destruction of dextran associate and change of their structure in biological media …”
Section: Introductionmentioning
confidence: 99%
“…Established by now main methods for dextran nanoparticle preparation include: the cross‐linking in reverse micelle (water–paraffin emulsion), however, in this case the particle sizes are difficult to control; the dextran oxidation, the multistage formation, and purification of dextran nanoparticles being the main disadvantage of this method; the self‐assembly of copolymers and conjugates based on dextran. This approach suggests the complicated synthetic procedures of dextran modification . Moreover, the absence of cross‐linking in the assemblies obtained may lead to the destruction of dextran associate and change of their structure in biological media …”
Section: Introductionmentioning
confidence: 99%
“…Besides this, HA has been widely used for the construction of tumor-targeting nanoparticles because it could specifically target CD44 receptors of tumor cells and facilitate cellular uptake (Huo et al, 2017 ; Cai et al, 2019 ; Zhang et al, 2020 ; Rangasami et al, 2021 ). The copolymer micelle is an amphiphilic molecule, which could self-assembly into a nanoparticle in aqueous solution (Zhang et al, 2016 , 2017 ). Structure-modified HA with hydrophobic molecules could form grafted amphiphilic copolymers and be used for micelle construction.…”
Section: Introductionmentioning
confidence: 99%
“…7 However, it has been reported that the extracellular pH of solid tumors is more acidic than normal tissues. 8,9 Choosing a pH-sensitive drug delivery system is one of the ideal options for adding specific tissue distribution undergoing chemotherapy, as it could increase the therapeutical efficacy and reduce adverse effects. Therefore, it is necessary for researchers to find a multifunction carrier for efficient drug delivery to the tumor regions.…”
Section: Introductionmentioning
confidence: 99%